Antibiotic Susceptibility Patterns for Carbapenem-Resistant Enterobacteriaceae. (20th February 2023) - Armin, Shahnaz; Fallah, Fatemeh; Karimi, Abdollah; Karbasiyan, Fereshteh; Alebouyeh, Masoud; Rafiei Tabatabaei, Sedigheh; Rajabnejad, Maryam; Mansour Ghanaie, Roxana; Fahimzad, Seyed Alireza; Abdollahi, Nafiseh; Khodaei, Hannan; Azimi, Leila
Abstract : Carbapenem is a broad-spectrum beta-lactam antibiotic considered the last choice for the treatment of antibiotic-resistant Gram-negative bacteria. Thus, the increasing rate of carbapenem resistance (CR) in Enterobacteriaceae is an urgent public health threat. This study aimed to evaluate the antibiotic susceptibility pattern of carbapenem-resistant Enterobacteriaceae (CRE) to new and old antibiotics. In this study, Klebsiella pneumoniae, E. coli, and Enterobacter spp. were collected from 10 hospitals in Iran for one year. CRE is recognized by resistance to meropenem and/or imipenem disk after identification of the collected bacteria. Antibiotic susceptibility of CRE against fosfomycin, rifampin, metronidazole, tigecycline, and aztreonam was detected by disk diffusion method and colistin by MIC. In this study, 1222 E. coli, 696 K. pneumoniae, and 621 Enterobacter spp. were collected from 10 hospitals in Iran in one year. Fifty-four E. coli (4.4%), 84 K. pneumoniae (12%), and 51 Enterobacter spp. (8.2%) were CRE. All CRE strains were resistant to metronidazole and rifampicin. Tigecycline has the highest sensitivity on CRE and levofloxacin for Enterobacter spp. Tigecycline showed an acceptable effectiveness rate of sensitivity on the CRE strain. Therefore, we suggest that clinicians consider this valuable antibiotic to treat CRE.